2017
DOI: 10.1002/biot.201600488
|View full text |Cite
|
Sign up to set email alerts
|

miR‐92a enhances recombinant protein productivity in CHO cells by increasing intracellular cholesterol levels

Abstract: BackgroundMicroRNAs (miRNAs) have emerged as promising targets for engineering of CHO cell factories to enhance recombinant protein productivity. Manipulation of miRNA levels in CHO cells have been shown to improve product yield by their effects on cellular processes such as increasing proliferation, resisting apoptosis and enhancing specific productivity (qP). We previously demonstrated increases in qP and titer of CHO-IgG cells by over-expressing miR-92a [1]. Stably-transfected pools showed 27% increase in q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Several miRNAs have proven to play a major role in BAT, such as controlling brown adipocytes differentiation [36]. Among these miRNAs, miR-92a has been involved in several metabolic processes, such as glucose homeostasis [24], regulation of intracellular cholesterol levels [37], and essential hypertension [38]. Furthermore, Chen and collaborators demonstrated that serum levels of exosomal miR-92a were inversely correlated with human BAT activity, confirming the data by FDG-PET/CT [39].…”
Section: Introductionmentioning
confidence: 70%
“…Several miRNAs have proven to play a major role in BAT, such as controlling brown adipocytes differentiation [36]. Among these miRNAs, miR-92a has been involved in several metabolic processes, such as glucose homeostasis [24], regulation of intracellular cholesterol levels [37], and essential hypertension [38]. Furthermore, Chen and collaborators demonstrated that serum levels of exosomal miR-92a were inversely correlated with human BAT activity, confirming the data by FDG-PET/CT [39].…”
Section: Introductionmentioning
confidence: 70%
“…Identifying mRNA targets of identified microRNAs enables researchers to understand the pathways and mechanisms that are involved in improving recombinant protein expression [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 39 , 40 , 42 , 43 , 45 , 49 , 50 , 52 , 53 , 56 ]. In addition to detecting the mRNA-microRNAs interactions, investigators performed additional bioinformatics research to identify biological processes, gene ontology, and significant pathways that are affected by the targeted microRNAs.…”
Section: Bioinformatics Methodologiesmentioning
confidence: 99%
“…In addition to detecting the mRNA-microRNAs interactions, investigators performed additional bioinformatics research to identify biological processes, gene ontology, and significant pathways that are affected by the targeted microRNAs. The researchers also aligned gene sequences between species, especially in the case of CHO cells where knowledge of genome is less evolved than that of the human genome [ 39 , 45 , 56 ]. These bioinformatics tools, also summarized in Table 2 , help to provide a comprehensive analysis, ensuring a robust approach to improving recombinant protein production.…”
Section: Bioinformatics Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, cholesterol regulation may also play a role on protein secretion reduction as it is an essential building block of secretion vesicles (Wang et al, 2000). Recently, it has been shown that the increase of cholesterol synthesis with the up-regulation of a micro RNA can increase the productivity of CHO cell lines by increasing their secretion capacity (Loh et al, 2017). It is then possible that the increase of productivity and glutathione content observed over time during the process are also link to cholesterol regulation.…”
Section: Discussionmentioning
confidence: 99%